Composition of agarose substrate affects behavioral output of Drosophila larvae - Apostolopoulou, Anthi A.; Hersperger, Fabian; Mazija, Lorena; Widmann, Annekathrin; Wüst, Alexander; Thum, Andreas S. (Frontiers in Behavioral Neuroscience, 2014)
In the last decade the Drosophila larva has evolved into a simple model organism offering the opportunity to integrate molecular genetics with systems neuroscience. This led to a detailed understanding of the functional neuronal networks for a number of sensory functions and behaviors including olfaction, vision, gustation and learning and memory. Typically, behavioral assays in use exploit simple Petri dish setups with either agarose or agar as a substrate. However, neither the quality nor the concentration of the substrate is generally standardized across these experiments and there is no data available on how larval behavior is affected by such different substrates. Here, we have investigated the effects of different agarose concentrations on several larval behaviors. We demonstrate that agarose concentration is an important parameter, which affects all behaviors tested: preference, feeding, learning and locomotion. Larvae can discriminate between different agarose concentrations, they feed differently on them, they can learn to associate an agarose concentration with an odor stimulus and crawl faster on a substrate of higher agarose concentration. Additionally, we have investigated the effect of agarose concentration on three quinine based behaviors: preference, feeding and learning. We show that in all cases examined the behavioral output changes in an agarose concentration-dependent manner. Our results suggest that comparisons between experiments performed on substrates differing in agarose concentration should be done with caution. It should be taken into consideration that the agarose concentration can affect the behavioral output and thereby the experimental outcomes per se potentially due to an increased escape response on more rigid substrates.